THE INFLUENCE OF INTERPROFESSIONAL COMMUNICATION ON PATIENT OUTCOMES: A STUDY OF HEALTH ASSISTANTS, MEDICAL SECRETARIES, AND HEALTH ADMINISTRATION PROFESSIONALS IN SAUDI ARABIA - Fehaid Salem A. Alanazi, Salman Salem A. Alanazi, Musad Owejan Matar Al-Anazi, Nemer Falaah Almutiri, Munif Ateeq Hayy Al-Rashidi, Mohammad Abdulrahman M. Aldeailej, Abdulmalik Abdulaziz M. Aldehishi, (Chelonian Research Foundation, 2022)
Effective interprofessional communication is crucial for delivering high-quality patient care and improving patient outcomes. This study aimed to investigate the influence of interprofessional communication on patient outcomes among health assistants, medical secretaries, and health administration professionals in Saudi Arabia. A mixed-methods approach was employed, combining a cross-sectional survey and semi-structured interviews. The survey assessed the perceived level of interprofessional communication and its impact on patient outcomes, while the interviews explored the experiences and perspectives of healthcare professionals regarding interprofessional communication. The findings revealed that effective interprofessional communication was positively associated with improved patient outcomes, including reduced medical errors, enhanced patient safety, and increased patient satisfaction. However, several barriers to effective interprofessional communication were identified, such as hierarchical structures, lack of mutual respect, and inadequate training in communication skills. The study highlights the importance of fostering a culture of collaboration and providing communication skills training to improve interprofessional communication and ultimately enhance patient outcomes in Saudi Arabian healthcare facilities. Keywords: interprofessional communication, patient outcomes, health assistants, medical secretaries, health administration professionals, Saudi Arabia